Fission yeast essential nuclear pore protein Nup211 regulates the expression of genes involved in cytokinesis. - Domenick Kamel; Ayisha Sookdeo; Ayana Ikenouchi; Hualin Zhong (PLoS ONE)
Nuclear pore proteins control nucleocytoplasmic transport; however, certain nucleoporins play regulatory roles in activities such as transcription and chromatin organization. The fission yeast basket nucleoporin Nup211 is implicated in mRNA export and is essential for cell viability. Nup211 preferentially associates with heterochromatin, however, it is unclear whether it plays a role in regulating transcription. To better understand its functions, we constructed a nup211 "shut-off" strain and observed that Nup211 depletion led to severe defects in cell cycle progression, including septation and cytokinesis. Using RNA-Seq and RT-qPCR, we revealed that loss of Nup211 significantly altered the mRNA levels of a set of genes crucial for cell division. Using domain analysis and CRISPR/cas9 technology, we determined that the first 655 residues of Nup211 are sufficient for viability. This truncated protein was detected at the nuclear periphery. Furthermore, exogenous expression of this domain in nup211 shut-off cells effectively restored both cell morphology and transcript abundance for some selected genes. Our findings unveil a novel role for Nup211 in regulating gene expression.